2017
DOI: 10.1002/smll.201702516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Irradiation on Dynamics of Charge Exchange Processes between Single Trap and Nanowire Channel

Abstract: In the present study, transport properties and single trap phenomena in silicon nanowire (NW) field-effect transistors (FETs) are reported. The dynamic behavior of drain current in NW FETs studied before and after gamma radiation treatment deviates from the predictions of the Shockley-Read-Hall model and is explained by the concept taking into account an additional energy barrier in the accumulation regime. It is revealed that dynamics of charge exchange processes between single trap and nanowire channel stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…37 Several reports have demonstrated that gamma radiation treatments modify the material properties by the self-controlled process and this characteristic effect can be used to develop materials with statistically stabilized and desired properties. 38,39 In order to gain a deep insight into the origin of the magnetization observed in the monolayer WS 2 , as shown in Fig. 5 (a), we performed DFT calculations using the projector-Augmentedwave method implemented in the Vienna ab initio simulation package (VASP).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…37 Several reports have demonstrated that gamma radiation treatments modify the material properties by the self-controlled process and this characteristic effect can be used to develop materials with statistically stabilized and desired properties. 38,39 In order to gain a deep insight into the origin of the magnetization observed in the monolayer WS 2 , as shown in Fig. 5 (a), we performed DFT calculations using the projector-Augmentedwave method implemented in the Vienna ab initio simulation package (VASP).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Silicon nanowire (NW) field‐effect transistors (FETs) are reliable and robust electronic devices with a huge potential in particular for applications in biosensors and bioelectronics due to the unique and tunable electrical properties of silicon nanowires . These devices demonstrate improved electrostatic control capabilities and outstanding transport properties, however there are still many critical issues such as short‐channel effects, increased low‐frequency noise, leakage current, and high‐field parasitic effects that give rise to new challenges in design and optimization of NW FET devices as well as in their practical applications including sensing . Among the above mentioned critical issues, an increased low‐frequency noise of scaled FETs is considered as a substantial drawback for their sensing applications determining resolution of the sensor .…”
Section: Introductionmentioning
confidence: 99%
“…When comes to Fig. 5(b), four current levels (i.e., L1, L2, L3, and L4) are clearly observed coming from the different trapping/de-trapping states (i.e., (00), (01), (10), and (11)) of TrapC and TrapD, respectively. As the gate voltage increases, there are only three current levels in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The RTN magnitudes including current fluctuation (i.e., ID) and threshold voltage fluctuation (i.e., Vth), have been recognized as dominant degradation factors affecting the performances of devices and circuits [6]- [8]. Moreover, understanding the voltage dependence of RTN magnitudes can provide valuable information in revealing the underlying physical mechanism and predicting time-dependent variability in circuit simulation [9], [10]. To extend the limited information within the measurement window, Franco et.…”
Section: Introductionmentioning
confidence: 99%